The significance of histological activity measurements in immune checkpoint inhibitor colitis. Issue 1 (4th November 2020) - Pai, Rish K.; Pai, Reetesh K.; Brown, Ian; Choi, Won‐Tak; Schaeffer, David F.; Farnell, David; Kumarasinghe, M. Priyanthi; Gunawardena, Dilini; Kim, Baek Hui; Friedman, Mark; Ghayouri, Masoumeh; Lauwers, Gregory Y.
Summary: Background: Colitis is a significant complication of immune checkpoint inhibitors (ICI). Currently, clinical and endoscopic severity are used to guide therapy. Aims: To investigate associations between clinical, endoscopic, and histological features with outcomes Methods: We identified 149 patients from seven institutions with biopsy‐proven ICI colitis. Biopsies were evaluated for histological features including the Geboes score, and the Robarts histopathological index (RHI) was calculated. Clinical, endoscopic, and histological data were tested for associations with biological use and adverse colitis outcomes (biological‐refractory colitis, colectomy or death from colitis). Results: Three mutually exclusive histological patterns were identified: acute colitis, chronic active colitis and microscopic colitis. Microscopic colitis was associated with older age (68.5 vs 61 years for acute colitis pattern, P  = 0.02) and longer time to colitis (5.5 vs 3 months for the other patterns, P  = 0.05). Biological use was associated with earlier time to colitis (2 vs 3 months, P  = 0.04) and higher RHI (18 vs 12, P  = 0.007). On multivariate analysis, RHI ≥14 was associated with biological use with an odds ratio of 4.5 (95% CI 1.4‐13.8; P  = 0.01). Adverse colitis outcomes were associated with shorter time to colitis (2 vs 3 months, P  = 0.008) and higher RHI (24 vs 14, P  = 0.001). On multivariate analysis, RHI ≥24 was associated with adverse colitis outcomes with an odds ratio 9.5 (95% CI 2.1‐42.3 P  = 0.003). Conclusion: Histological activity as measured by RHI is the only factor independently associated with biological use and adverse colitis outcomes. Prospective studies are needed to validate these findings to determine if histological activity should be incorporated into therapeutic algorithms.